Community Structure of Mangrove in Sungai Alam Village Bengkalis Sub Regency, Bengkalis Regency, Riau Province - Elfrida Hasugian; Adriman '; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
A study aims to understand the community structure of mangrove that grow in the SungaiAlam village, Riau has been conducted from January to February 2014. Sampling was doneusing a line plot sampling method. Mangrove in the sampling sites were divided in to seedling,sapling, poles and trees. Mangroves were identified based on Rusila at al (2006), Bengen (2001)and Saparinto (2007). While data were analized following English, Wilkinson, and Baker (1994).Results shown that there were 10 mangrove types (8 families) present in the samplingarea they were Avicennia alba, Sonneratia alba, Acanthus ilicifolius, Acrostichum speciosum,Rhizophora mucronata, Rhizophora stylosa, Rhizophora apiculata, Nypa fruticans, Lumnitzeraracemosa and Xylocarpus granatum. The dominant species in the research area is Rhizophoraspp. Mangrove distribution on this research influenched by sediment types. Mangrove vegetationdominated by Avicennia spp. and Sonneratia spp. in the deep muddy area. While in the shallowmuddy area, it was dominated by Rhizophora spp. In the dry area Xylocarpus spp., Rhizophoraspp., and Nypa spp. were dominant. Shannon and Winner index of the mangrove ranged from0,66-1,92 and dominancy index (C) ranged from 0,36-0,1. Temperature ranged 28-30oC, land pH6, water pH ranged 6-7, and salinity ranged 21-22o/oo.Keyword : Mangrove, Community structure, Sungai Alam Village